2020
DOI: 10.1101/2020.12.08.407247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noncanonical usage of stop codons in ciliates expands proteins with Q-rich motifs

Abstract: Intrinsically disordered regions (IDRs) are protein sequences lacking fixed or ordered three-dimensional structures. Many IDRs are endowed with important molecular functions such as physical interactions, posttranslational modifications or solubility enhancement. We reveal that several biologically important IDRs can act as N-terminal fusion carriers to promote target protein folding or protein quality control, thereby enhancing protein expression. This nanny function has a reasonably strong correlation with h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…Intriguingly, all the above-mentioned N-IDRs in the non-DDR proteins also possess at least one S/T-Q motif that may be susceptible to phosphorylation by Mec1 ATR and Tel1 ATM . For instance, phosphorylation of Sup35-S 17 Q in response to DNA lesions has been assessed in immunoblots (Chuang et al 2020). Therefore, we have proposed the "N-terminal intrinsic disorder facilitates abundance" (NIDFA) hypothesis that N-IDRs with high S/T/Q/N contents facilitate protein folding and some could be subject to proteostasis controlled by Mec1 ATR and Tel1 ATM due to the sporadic emergence of S/T-Q motifs (Chuang et al 2020).…”
Section: Intrinsic Structural Disorder Is Critical For the Nanny Function Of Rad51-ntdmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, all the above-mentioned N-IDRs in the non-DDR proteins also possess at least one S/T-Q motif that may be susceptible to phosphorylation by Mec1 ATR and Tel1 ATM . For instance, phosphorylation of Sup35-S 17 Q in response to DNA lesions has been assessed in immunoblots (Chuang et al 2020). Therefore, we have proposed the "N-terminal intrinsic disorder facilitates abundance" (NIDFA) hypothesis that N-IDRs with high S/T/Q/N contents facilitate protein folding and some could be subject to proteostasis controlled by Mec1 ATR and Tel1 ATM due to the sporadic emergence of S/T-Q motifs (Chuang et al 2020).…”
Section: Intrinsic Structural Disorder Is Critical For the Nanny Function Of Rad51-ntdmentioning
confidence: 99%
“…For instance, phosphorylation of Sup35-S 17 Q in response to DNA lesions has been assessed in immunoblots (Chuang et al 2020). Therefore, we have proposed the "N-terminal intrinsic disorder facilitates abundance" (NIDFA) hypothesis that N-IDRs with high S/T/Q/N contents facilitate protein folding and some could be subject to proteostasis controlled by Mec1 ATR and Tel1 ATM due to the sporadic emergence of S/T-Q motifs (Chuang et al 2020). Our NIDFA hypothesis could account for the functions of proteins that harbor an N-IDR but lack binding partners or that fold prior to protein-protein interaction, distinguishing it from two interesting hypothetical models that have been proposed previously.…”
Section: Intrinsic Structural Disorder Is Critical For the Nanny Function Of Rad51-ntdmentioning
confidence: 99%
“…For instance, phosphorylation can stabilize the tertiary structural organization of the IDR while enhancing and stabilizing its binding to the protein's ligand (Gsponer et al, 2008;Nishi et al, 2011). Bioinformatic analysis has suggested that this function is tunable by PTMs and correlated with a high content of serine, threonine, glutamine and asparagine (Chuang et al, 2020).…”
Section: Bht N-terminal Idr Compositionmentioning
confidence: 99%